Investigation the Effect of Negative Polarity of Surface Roughness and Metal Removal Rate During EDM Process - Shahd Taqi; Saad Shather (Engineering and Technology Journal, 2020)
The Electro discharge machine that named (EDM) is used to remove the metal from the workpiece by spark erosion. The work of this machining depends on the multiple variables. One of the most influential variants of this machine is the polarity, the material of the electrode, the current and the time pulses. Essentially the polarity of the tool (electrode) positive and the work piece is negative, this polarity can be reversed in this paper was reversed the polarity that was made the tool (electrode) negative and the work piece was positive. The aim of this paper was focused on the influence of reversed the polarity (negative) with changing the electrode metal (copper and graphite) on the surface roughness and metal removal rate by using different parameters (current and pulses of time). Experiments show that: the copper electrode gives (best surface roughness 0.46 μm when the current 5 Am and Ton 5.5 μs) and (worst surface roughness 1.66 μm when the current is 8 A and Ton 25 μs). And give (best values of the MRR 0.00291 g/min when the current is 8 and Ton 25 μs) and (The lowest values of MRR (0.00054 g/min when current is 5 and Ton 5.5 μs). The graphite electrode gives (best surface roughness 2.07 μm when the current 5 Am and Ton 5.5 μs) and (worst surface roughness 4.17 μm when the current is 8 A and Ton 25 μs). And give (best values of the MRR 0.05823 g/min when the current is 8 and Ton 25 μs) and (The lowest values of MRR (0.00394 g/min when current is 5 and Ton 5.5 μs).